Influence of the nature of the methyling agent and solvent on the directions of the methylation reaction of 2-methylqinazolin-4-ones - Foziljon Ergashevich Saitkulov; Burkhon Juraevich Elmuradov (Genius Journals, 2023)
It is known that methylation of pyrimidine and quinazoline derivatives proceeds in different directions with the formation of one or two isomers. So, if 2-methilquinazolin-4-one is methylated at the N-1 and N-3 atom or simultaneously at these two centers, then methylation of 2-methyilquinazolin-4-one occurs mainly at the “softer” reaction center
Keywords: methylation; quinazoline; pyrimidine; methilquinazolin